2021
DOI: 10.1021/acs.jmedchem.0c01826
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Encequidar, First-in-Class Intestine Specific P-glycoprotein Inhibitor

Abstract: Many chemotherapeutics, such as paclitaxel, are administered intravenously as they suffer from poor oral bioavailability, partly because of efflux mechanism of P-glycoprotein in the intestinal epithelium. To date, no drug has been approved by the U.S. Food and Drug Administration (FDA) that selectively blocks this efflux pump. We sought to identify a compound that selectively inhibits P-glycoprotein in the gastrointestinal mucosa with poor oral bioavailability, thus eliminating the issues such as bone marrow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 75 publications
(123 reference statements)
0
29
1
Order By: Relevance
“…Low bioavailability has also been reported for the intestine-specific P-gp inhibitor, encequidar (HM30181) ( Kwak et al, 2010 ; Paek et al, 2006 ; Smolinski et al, 2021 ). Low oral bioavailability of encequidar was a key feature in the development to ensure a local intestinal effect with minimal systemic effects, and was emphasised as a potential advantage over other P-gp inhibitors, like tariquidar, elacridar, and zosuquidar ( Smolinski et al, 2021 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Low bioavailability has also been reported for the intestine-specific P-gp inhibitor, encequidar (HM30181) ( Kwak et al, 2010 ; Paek et al, 2006 ; Smolinski et al, 2021 ). Low oral bioavailability of encequidar was a key feature in the development to ensure a local intestinal effect with minimal systemic effects, and was emphasised as a potential advantage over other P-gp inhibitors, like tariquidar, elacridar, and zosuquidar ( Smolinski et al, 2021 ).…”
Section: Resultsmentioning
confidence: 97%
“…Low bioavailability has also been reported for the intestine-specific P-gp inhibitor, encequidar (HM30181) ( Kwak et al, 2010 ; Paek et al, 2006 ; Smolinski et al, 2021 ). Low oral bioavailability of encequidar was a key feature in the development to ensure a local intestinal effect with minimal systemic effects, and was emphasised as a potential advantage over other P-gp inhibitors, like tariquidar, elacridar, and zosuquidar ( Smolinski et al, 2021 ). However, in the present study, zosuquidar elicited similar oral absorption to encequidar with bioavailabilities of 4.12 and 6.25%, respectively, as well as C max values of 10.9 and 7.1 ng/mL after 6.3 mg/kg zosuquidar and 10 mg/kg encequidar, respectively ( Smolinski et al, 2021 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Here, the dosing requires that patients are in the fasted state and take one tablet of the P-gp inhibitor encequidar. Then, one hour later, patients take multiple capsules of paclitaxel as a bio-enhanced formulation [44]. This case study illustrates the clinical importance of the acute response of efflux transporters.…”
Section: Discussionmentioning
confidence: 91%
“…Performed molecular docking studies demonstrated that all evaluated triterpenoids could properly fit into the transmembrane domain of the listed transporters with low binding energies, forming hydrogen bonds with key amino acid residues crucial for the pump activity of these proteins ( Figure 2 D): In the case of P-glycoprotein, SM and αO-SM formed a hydrogen bond with Tyr307, which is involved in regulating the ATP hydrolytic activity of the protein [ 36 ] and is a major interaction partner of the novel benzophenone sulfonamide-based inhibitor of P-glycoprotein [ 37 ]. The binding pockets of SM and SM epoxides were also found to involve a hydrogen bond with Gln347, which is a well-known inhibitor-binding residue in P-glycoprotein [ 38 , 39 , 40 ]. In the case of MRP1, αO-SM formed a hydrogen bond with Arg1248, playing an important function in the positioning of substrates within the drug-binding pocket of the protein [ 41 , 42 ] and involving the amino acid interaction network of the novel flavonoid-based inhibitor of MRP1 [ 43 ].…”
Section: Resultsmentioning
confidence: 99%